Study on the Ground Fissure Development Law of Coal Mining Based on UAV Photogrammetry and the Particle Flow Theory - Zhang, Yanjun; Kong, Jiayuan; Long, Sifang; Zhu, Yuanhao; Zhu, Wenxin; Wu, Tianhui (Frontiers in Environmental Science, 2022)
Ground fissures caused by underground coal seam mining easily result in secondary geological disasters and destroy the ecological environment, which seriously impacts the production and life of mining areas and residents. The traditional monitoring methods, such as manual measurement and satellite monitoring, have their disadvantages. Therefore, it is urgent to develop a large-scale monitoring technology for ground fissures and study its development law. In this article, we analyzed the distribution characteristics of ground fissures based on the low-altitude UAV remote sensing images and combined them with field investigation as validation. Moreover, we introduced the particle flow theory to study the development law and formation mechanism of ground fissures. This article takes the 8092 working face of a mine in Ordos City as the study area. The results showed that the accuracy rate of ground fissures based on the visual interpretation of UAV images was 95%. The ground fissures were mainly distributed near the stopping line and the groove of the working face. The plane forms of ground fissures were mainly two types: the linear type and arc type, and the location relationship can be divided into the parallel type and bifurcation type. The types of ground fissures were the tensile type and step type. Whether the upper and lower parts of the key strata were broken simultaneously is the root cause of tensile ground fissures and step ground fissures. The stability of the overlying strata had a significant influence on the change of abutment pressure above the goaf. The process of surface movement and deformation can be divided into three stages: tensile failure of the slope bottom, traction failure of the slope body, and sliding failure of the slope top. In addition, the zero point of the surface horizontal movement value and the maximum surface subsidence were not in the center of the goaf. Due to the horizontal slip of the downhill direction in the horizontal movement on the surface, the value of the downhill direction subsidence was zero. However, the value of the horizontal movement was not zero, and there was even a large horizontal movement. In conclusion, the research results can provide a useful reference for the rapid monitoring of large-scale geological disasters caused by underground coal seam mining and the application of the particle flow theory.